An examination of father types and the subsequent framing of coach–father relationships in English youth football through the eyes of an expert coach. (19th May 2018) - Magee, Jonathan
Abstract : The 2014 FIFA World Cup produced a poor performance by England which reinforced the view of Gary Lineker, former England captain turned media pundit, that the youth development system was failing and that a 'parental cultural revolution' was a necessary element for future improvement. This paper researches fathers in English youth football from the perspective of an expert coach with two aims in mind. Firstly, the paper will identify more father types than the one Lineker based his revolution on. Secondly, the paper will discuss how different father types subsequently frame different coach–father relationships. The paper concludes by recommending that the UEFA Coach Accreditation system embeds knowledge of different father types and the subsequent different coach–father relationships in their courses to assist future coaches. Lastly, there is a call for further research to be carried out into father/parent types in youth sport, especially from the perspective of coach.